Effect of Gross Domestic Product and Exchange Rate on Rice Export Promotion and Competitiveness in Nigeria: 2000-2023 - Idisi, P.O.; Ebukiba, E.S.; Maduekwe, I.M.; Adeagbo, B.A.; Salihu, M.U.; Shuaib, R.; Usman, H.; Mohammad, M.; Amarachi, O.; Abiodun, O.O.; Isike, G.O. (European Scientific Journal, ESJ, 2026)
This study investigated the effects of GDP and exchange rate on rice export promotion in Nigeria from 2000 to 2023. The study employed time series data. The Ordinary Least Squares (OLS) and Autoreggressive Distributed Lag methods (ADLM) were used for the estimation of the models. The variables are stationary at level. The result of the trend estimation shows positive and significant trend at (P>1%) for exchange rate and rice export. Furthermore, the result of the trend estimation shows negative and significant trend at (P>1%) for Gross Domestic Product. The estimated Ordinary Least Square result shows that the coefficient of exchange rate (EXR) is negative and significant at (P>10%). The result also shows that the coefficient of Gross Domestic Product (GDP) is positive and significant at (P>10%). The estimated Autoreggressive distributed lag result shows that the coefficient of exchange rate (EXR) and GDP (-1) is negative and significant at (P>5%). The result further shows that the coefficient of GDP, GDP(-2) and rice export(-2) is positive and significant at (P>5%). The result shows that there is causality from exchange rate to gross domestic product. It also shows that there is no causality from exchange rate and GDP to rice export implying that rice export is not competitive. Therefore this study recommends that the Government develops export-friendly policies, negotiate trade agreements, and explore partnerships to gain access to international markets for Nigerian rice. Also, attract private sector investments in the rice value chain, from production to processing and marketing, so as to enhance competitiveness.